What is at stake in the narrative of the guests of philosophical practice? - Lindseth, Anders (Array, 2021)
In the dialogues of Philosophical Practice, the philosopher has to continuously ask himself or herself what is at stake in the narratives of the guests. What are their stories really about? Special, responsive attention is required in such dialogues. This paper is an attempt to clarify the difference between a philosophical dialogue and other dialogues, such as ordinary everyday dialogues and dialogues with experts, especially with professional helpers. Philosophical Practice is understood as being about interpreting a guest’s message as self-communication, while outside the practice room, it is usually experienced and seen as a form of address or information. It is a challenge of ethical nature that the Philosophical Practitioner can open up a space of attention in the dialogue where the self-communication of the guest may be perceived anew and thus making possible a new orientation in life. Philosophical Practice is aiming at freeing such self-communication from discourse and locating it in nature and freedom.